2018
DOI: 10.1002/pola.29001
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane elastomers based on amphiphilic poly(caprolactone)‐b‐poly(butadiene)‐b‐poly(caprolactone) triblockcopolyols

Abstract: Hydroxyl-terminated poly(butadiene) (HTPB; M n 5 2100 g mol 21 ) was capped with 30 and 60 wt % of E-caprolactone to reach amphiphilic triblock copolymers in form of capped poly(butadiene) CPB. The former (CPB30; M n 5 3300 g/mol) is amorphous with a glass temperature of 256 8C. CPB60 (M n 5 4000 g mol 21 ) is semi-crystalline with a melting point of 50 8C and a glass transition at 247 8C. The CPBs, HTPB and polycaprolactone diol (M n 5 2000 g mol 21 ) were used as soft segment components in the preparation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, the unique "bottle brushes" structure of PFD makes PUEs exhibit a lower T g, SS than that of most HTPB-based PUEs with similar HS composition and HSC. 35,39 As shown in Figure 4 and Table III, △H MMT and △H M increased with the increasing of HSC. This indicated that the increase of average HS length favors the formation of mixed phase and well-ordered HS phase.…”
Section: Dsc Analysismentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, the unique "bottle brushes" structure of PFD makes PUEs exhibit a lower T g, SS than that of most HTPB-based PUEs with similar HS composition and HSC. 35,39 As shown in Figure 4 and Table III, △H MMT and △H M increased with the increasing of HSC. This indicated that the increase of average HS length favors the formation of mixed phase and well-ordered HS phase.…”
Section: Dsc Analysismentioning
confidence: 73%
“…Prominent extent of phase separation might be the main reason that causes virtually constant values of T g , SS and T g , HS . Moreover, the unique “bottle brushes” structure of PFD makes PUEs exhibit a lower T g , SS than that of most HTPB‐based PUEs with similar HS composition and HSC . As shown in Figure and Table , ▵ H MMT and ▵ H M increased with the increasing of HSC.…”
Section: Resultsmentioning
confidence: 92%
“…Shore A hardness of PUEs corresponding to different contents of chromogen is largely inuenced by the content and the morphology of the hard phase, and the values are consistent with so rubbers. 34 The hardness of the PUE lms are affected by many factors such as H-bonding, phase separation and crosslink density. In contrast, the Shore A hardness for BPUE 10 (10% molar ratio chromogen) is much lower (Shore A 61.7), which may be caused by an overdose of chromogen affecting hydroxyl activity.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…Polyurethane is an interesting polymer applied for a range of applications in different forms as elastomer, thermoplastic, sponges, and foams . For most of the applications in the biomedical field, textile, shoe sole, mattresses, adhesives, and so on, antibacterial property adds on to its properties profile …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Polyurethane is an interesting polymer applied for a range of applications in different forms as elastomer, thermoplastic, sponges, and foams. [11][12][13][14][15][16] For most of the applications in the biomedical field, textile, shoe sole, mattresses, adhesives, and so on, antibacterial property adds on to its properties profile. 17,18 The metal and metal oxide nanoparticles, such as silver, copper, Ni, and ZnO can be either extruded with PU or used during in situ formation of PU to achieve antibacterial activity.…”
mentioning
confidence: 99%